Veterinary service to control leptospirosis - Mansurova Malika Khasanovna; Nematov Aminzhon Sabdarovich (Universitas Muhammadiyah Sidoarjo, 2022)
Leptospirosis is a naturally occurring infectious disease caused by bacteria of the genus Leptospira that infect wild, domestic, and human animals. The disease is characterized by damage to the capillaries, liver, kidneys, muscles, nervous system and fever. Due to the complexity of clinical and laboratory diagnosis of leptospirosis, epidemiological surveillance is somewhat difficult, so it is carried out only by specialists in the epidemiology department of the DSENM in the city (major cities) and regions (Republic). This control is most effective when carried out in conjunction with the veterinary service.